Ptilopachinae: a new subfamily of the Odontophoridae (Aves: Galliformes) - Bowie, Rauri C.k.; Cohen, Callan; Crowe, Timothy M. (Zootaxa, 2013)
The use of DNA sequences of diverse genetic loci has revolutionized our understanding of the systematic relationships among many different organisms. One such unexpected discovery was that two African galliform species, the Stone Partridge Ptilopachus petrosus Gmelin, 1789, and Nahan’s Francolin Francolinus nahani Dubois, 1905, represent a relictual clade sister to the New World Quail (Odontophoridae) and hence are only distantly related to other Old World Galliformes (Crowe et al. 2006, Cohen et al. 2012). Almost as unexpected was the recovery of the sister relationship between P. petrosus and F. nahani, which had never been considered close relatives, much less placed in the same genus (Crowe et al. 2006, Cohen et al. 2012). Previously unrecognized vocal and behavioral similarities between P. petrosus and P. nahani supported the genetic data and the transfer of nahani to Ptilopachus (Crowe et al. 2006, Cohen et al. 2012). Intriguingly, both species occupy areas suggested to serve both as centres of species diversification and places where relictual taxa persist (Kingdon 1989, Fjeldså & Bowie 2008, Fjeldså et al. 2012): P. nahani in dense primary forest in the vicinity of the Albertine Rift and P. petrosus in rocky outcrops of the Sahel.